Comparison of absolute neutrophil count between premature and term infants - Ahmad Faisal; Guslihan D Tjipta; Bidasari Lubis; Dachrul Aldy (Indonesian Pediatric Society, 2004)
Background Neutrophils are very important in the body defenseagainst bacterial infection. Absolute neutrophil count (ANC) couldbe used for the recognition of early-onset bacterial sepsis inneonates.Objective The aim of this study was to compare the value of ANCbetween premature and term infants, to assess the prevalence ofearly-onset neutropenia in premature infants and its relationshipwith prematurity, and to find out the correlation between gesta-tional age and ANC.Methods A cross-sectional study was conducted during Februaryto May 2003. Subjects were newborn infants with gestational ageof less than 37 weeks who were born in Adam Malik and PirngadiHospitals, Medan. Newborn infants with severe asphyxia (5-minuteApgar score of less than 4), fever, seizure, and maternalhypertension were excluded. Complete blood count was done bymeans of automatic cell counter (Micros (R) , Germany). Term healthyinfants were used as control subjects.Results ANC differed significantly between both groups (p=0.0001).The prevalence of early-onset neutropenia in premature infantswas 9% (95%CI 0.065;0.21). Prematurity was related with theincidence of neutropenia with a prevalence ratio of 1.1. Therewas a weak positive correlation between gestational age andANC with an r-value of 0.49 (p=0.0001).Conclusions ANC in premature infants differs from that in terminfants. The prevalence of early-onset neutropenia in prematureinfants was 9% (95%CI 0.065;0.21). Prematurity is related with theincidence of early-onset neutropenia in newborn infants. There isa correlation between gestational age and ANC